PENCEMARAN NITRAT DI AIRTANAH KECAMATAN GAMPING, KABUPATEN SLEMAN, DIY - , YOGA PURBAYA A.W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Water is the most important natural resources for human life . For their intended use, water is used for consumption, cleaning media, agricultural and industrial purposes as well. In order to meet these needs, the water must meet certain quality standards or free from all kinds of pollutants as a result of pollution. Human activities such as domestic sewage, agriculture, and industry, have a major role as a cause of water pollution. Nitrate is a compound that produced many of the chemical processes in the waste and dirt result of human activity. Nitrates can be a threat to humans because nitrate can lower water quality, lowering dissolved oxygen, foul odors, and bad taste. Gamping subdistrict is a region that borders the city of Yogyakarta. Growth and development locations in this area are quite rapidly. However, research on nitrates in groundwater has not been done. From the results of the laboratory analysis of groundwater samples in the study site, obtained the highest nitrate concentration was 108.97 mg / L contained in Ronggahan village, while the lowest values of nitrate concentration of 0.893 mg / L in the Patukan village. High and low values of nitrate concentrations in the study site is influenced by the hydrogeological conditions (depth of water table, types of aquifers, groundwater flow), rainfall, age of the study site, and the type of land use. Type of aquifer affect on permeability and porosity values, where the rocks that making up the porous and large fractures aquifers tend to have low nitrate concentrations, because of groundwater into the aquifer just passed involuntarily. Groundwater flow will affect the local distribution of the groundwater, if encountered high nitrate concentration in one location, but there is no strong parameters that can be used as the reason for the high value, could have groundwater flow at the site already carries a high flow of nitrate concentration elsewhere. Types of land use have a vertical effect on the value of nitrate concentration. Nitrate concentration was found to be much larger in the residential land use than in rice fields. All parameters cannot be considered separately in order to determine the main factors controlling the high and low concentrations of nitrate in the study site, but thay must be linked to each other.